2021
DOI: 10.1016/j.cegh.2021.100763
|View full text |Cite
|
Sign up to set email alerts
|

The predictors of high titer of anti-SARS-CoV-2 antibody of convalescent plasma donors

Abstract: Background Recent evidence suggested that the higher titers of anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody from convalescent plasma donors contributed to the clinical improvement in coronavirus disease 2019 (COVID-19) patients. However, the titers of anti -SARS-CoV-2 antibodies varied in each individual, and the precise factors that might govern such variation have not been elucidated. Objectives To assess the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
4
14
0
Order By: Relevance
“…We checked whether serological titer alone could represent an excellent predictive factor. Similar to previous studies [36][37][38] , we found higher NAb titers in older male patients with higher BMI, longer-lasting fever, and higher body temperature. Our search for an optimal prediction model showed that the most crucial predictor of a suitable CCP donor was the result of the serological Abbott Quant test.…”
Section: Discussionsupporting
confidence: 91%
“…We checked whether serological titer alone could represent an excellent predictive factor. Similar to previous studies [36][37][38] , we found higher NAb titers in older male patients with higher BMI, longer-lasting fever, and higher body temperature. Our search for an optimal prediction model showed that the most crucial predictor of a suitable CCP donor was the result of the serological Abbott Quant test.…”
Section: Discussionsupporting
confidence: 91%
“…According to the obtained results, the presence of dyspnea in the acute phase of COVID-19 increased the probability of persisting IgG seropositivity in the following months. This is consistent with the findings of studies from the US (n = 250) and Indonesia (n = 83) conducted among COVID-19 convalescent plasma donors, in which a history of dyspnea was significantly related to protective anti-SARS-CoV-2 IgG titers [10,11]. The odds ratio (OR) of dyspnea for IgG seropositivity determined in the US study was 1.61, i.e., similar to the present work (Table 1) [10].…”
Section: Discussionsupporting
confidence: 90%
“…In available studies, other symptoms, most commonly fever, were also identified as predictors of anti-SARS-CoV-2 IgG [10][11][12]. Since almost all symptomatic subjects experience more than one symptom, combinations of symptoms need to be evaluated too.…”
Section: Discussionmentioning
confidence: 99%
“…Karuna et al found that neutralizing antibody levels were higher in individuals recovering from severe COVID-19, with diabetes and lower in people with hypertension [ 17 ]. In a study searching for the predictors of high titer of anti-SARS-CoV-2 antibody of convalescent plasma donors, the authors pointed out that although high antibody titers were present, the antibody titer was not affected by comorbidities of donors [ 18 ].…”
Section: Discussionmentioning
confidence: 99%